THE USE OF LOVE COINS REWARDS TO FOSTER INDEPENDENCE IN CHILDREN AGED 5-6 YEARS: A CASE STUDY - Sindy Anugerah (Magister Scientiae, 2025)
This case study research aims to explain how giving Love Coins Rewards affects the independence of children aged 5-6 years. The method used in this research is a qualitative case study approach. A study that explores a problem with detailed boundaries, takes in-depth data, and includes various existing sources of information. Data was collected through observation, in-depth interviews with teachers and parents, as well as documentation of children's daily activities. Data analysis techniques used to process research data according to Miles, Huberman, and Saldana are data condensation, data display, and conclusions or verification. The research results show that the implementation of the Love Coins Reward system significantly motivates children to increase their independence at school. Children who get rewards show self-confidence, initiative, and the ability to make decisions independently. These findings indicate that using lovecoin as a form of appreciation can be an effective strategy in supporting the development of independence in early childhood. It is recommended that similar programs be integrated into learning activities in kindergarten with full support from teachers and parents to create a learning environment that is conducive to the formation of children's character and independence.